2015
DOI: 10.1371/journal.pone.0122843
|View full text |Cite
|
Sign up to set email alerts
|

WIN 55,212-2, Agonist of Cannabinoid Receptors, Prevents Amyloid β1-42 Effects on Astrocytes in Primary Culture

Abstract: Alzheimer´s disease (AD), a neurodegenerative illness involving synaptic dysfunction with extracellular accumulation of Aβ1-42 toxic peptide, glial activation, inflammatory response and oxidative stress, can lead to neuronal death. Endogenous cannabinoid system is implicated in physiological and physiopathological events in central nervous system (CNS), and changes in this system are related to many human diseases, including AD. However, studies on the effects of cannabinoids on astrocytes functions are scarce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 88 publications
6
34
0
Order By: Relevance
“…In agreement with this evidence, the Aβ‐induced hemichannel opening was strongly reduced by inhibiting p38 MAP kinase or iNOS, suggesting that the preventive influence of CBs on astroglial hemichannel activity may proceeds by decreasing the production of IL‐1β, TNF‐α, and NO. Similar inhibitory responses on NO production, activation of p38 MAP kinase and cytokine release have been described for CBs in activated astrocytes (Ortega‐Gutierrez et al, ; Sheng et al, ), even in those stimulated with Aβ (Aguirre‐Rueda et al, ). An alternative mechanism of hemichannel regulation to that resulting from covalent modifications (e.g., phosphorylation and/or S‐nitrosylation) is the sorting of hemichannels to the cell surface.…”
Section: Discussionsupporting
confidence: 68%
“…In agreement with this evidence, the Aβ‐induced hemichannel opening was strongly reduced by inhibiting p38 MAP kinase or iNOS, suggesting that the preventive influence of CBs on astroglial hemichannel activity may proceeds by decreasing the production of IL‐1β, TNF‐α, and NO. Similar inhibitory responses on NO production, activation of p38 MAP kinase and cytokine release have been described for CBs in activated astrocytes (Ortega‐Gutierrez et al, ; Sheng et al, ), even in those stimulated with Aβ (Aguirre‐Rueda et al, ). An alternative mechanism of hemichannel regulation to that resulting from covalent modifications (e.g., phosphorylation and/or S‐nitrosylation) is the sorting of hemichannels to the cell surface.…”
Section: Discussionsupporting
confidence: 68%
“…Whilst these findings at least superficially agree with some previous studies, 24 others have indicated that A β 1–42 does not alter astrocyte viability, 23 but can disrupt [Ca 2+ ] i 20 . These latter findings contrast with our observations both on viability (Figure 1) and alterations in [Ca 2+ ] i (Figure 2).…”
Section: Discussionsupporting
confidence: 92%
“…Within the glia, astrocytes are the cell type prevalent in the brain [29]. Astrocytes increase neuronal viability and mitochondrial biogenesis, protecting neural cells from oxidative stress and inflammation induced by the toxic amyloid peptide [30][31][32]. Conversely, if chronic inflammation occurs, astrogliosis is triggered, produced by a reaction to inflammation and oxidative stress caused by toxic and inflammatory agents [33].…”
Section: Interest Of the Reviewmentioning
confidence: 99%
“…Neurons have fewer defenses against ROS than astrocytes and cooperation between them is important for neuronal resistance against ROS [30,142,143]. Astrocytes contribute to the survival of neurons by detoxifying the ROS enzymes (GSH peroxidase and catalase), increasing antioxidant proteins (GSH or glutathione, vitamin E and ascorbate) and the biogenesis of mitochondria and reducing the activity of metals which can produce redox [31,[144][145][146]. The most powerful antioxidant protein in the brain is GSH produced by astrocytes and neurons, but neurons depend on astrocytes because they do not use extracellular cysteine efficiently and, therefore, need astrocytes to supply it.…”
Section: Oxidative Stress Ad and The Protective Role Of Astrocytes mentioning
confidence: 99%